THE CONCEPT OF INTEGRAL EDUCATION IN THE QUR'AN, SURAH AL-BAQARAH, VERSES 30–32: A STUDY OF AL-MANAR'S TAFSIR ON THE VERSES CONCERNING TARBIYAH - Ana Aulia Hanhifa; Enjang Burhanudin Yusuf (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the integration of educational concepts in Tafsir Al-Manar with reference to Surah Al-Baqarah verses 30–32 and to explore their implications for the development of a love-based curriculum. These verses contain fundamental educational values concerning the creation of humankind as khalifah (vicegerent) on earth, the process of imparting knowledge, and the acknowledgment of human limitations before the Creator. This study employed a qualitative method using a library research approach. Data were collected from primary sources, namely Tafsir Al-Manar and the Qur'an, particularly Surah Al-Baqarah verses 30–32, as well as secondary sources, including theses, books, and scholarly journal articles related to Islamic education, educational exegesis, and love-based curriculum. The findings reveal that the integration of educational concepts in Tafsir Al-Manar concerning Surah Al-Baqarah verses 30–32 has four major implications for the development of a love-based curriculum. First, it emphasizes the spiritual dimension as the foundation of education. Second, it promotes the balanced development of reason and knowledge. Third, it fosters the formation of moral and spiritual character. Fourth, it strengthens harmonious relationships among human beings and with the environment. The love-based curriculum derived from the perspective of Tafsir Al-Manar integrates love for Allah, love for knowledge, love for fellow human beings, and love for the natural environment as the foundational principles of a holistic educational process.